2022
DOI: 10.21203/rs.3.rs-2156016/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The road of >1000 corpses: landscape and road-related features that promote mortality in the Amazon

Abstract: Roads impact wildlife around the world; however, dedicated studies are lacking in many biodiverse areas such as the Amazon. Identifying which species are more often hit by vehicles and which landscape and road-related features promote roadkill is essential to guide future development and ensure adequate mitigation actions. For six months, we monitored 240 km of roads in the Ecuadorian Amazon and recorded 1125 dead vertebrates (148 species). Reptiles were the most affected class with 380 individuals (56 speci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 50 publications
(35 reference statements)
0
4
0
Order By: Relevance
“… Ecuadorian road network (primary and secondary roads) highlighting the sites and roads where systematic studies were conducted and the total number of roadkill records per taxonomic class across all studies. For the Napo province, the study area of Medrano‐Vizcaíno, Brito‐Zapata, and González‐Suárez ( 2022 ) covers most of this province (thick purple line), overlapping with the study areas by Filius et al ( 2020 ) and Medrano‐Vizcaíno and Espinosa ( 2021 ), both shown with a white line. …”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“… Ecuadorian road network (primary and secondary roads) highlighting the sites and roads where systematic studies were conducted and the total number of roadkill records per taxonomic class across all studies. For the Napo province, the study area of Medrano‐Vizcaíno, Brito‐Zapata, and González‐Suárez ( 2022 ) covers most of this province (thick purple line), overlapping with the study areas by Filius et al ( 2020 ) and Medrano‐Vizcaíno and Espinosa ( 2021 ), both shown with a white line. …”
Section: Resultsmentioning
confidence: 76%
“…We compiled 3305 wildlife roadkill records from 10 systematic surveys conducted on Ecuadorian roads. These corresponded to five published papers, four theses, and one unpublished dataset (Medrano‐Vizcaíno, Brito‐Zapata, & González‐Suárez, 2022 ). Georeferenced data were available for eight of these studies and comprised 2744 roadkill records.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations